Songs of Life and Death in Walker Percy’s Lancelot (1977) - Anastasija Ropa (Baltic Journal of English Language, Literature and Culture)
Cultures of life and death are central to the writing of American Southern novelist Walker Percy (1916–1990), and they are drawn with special force in his early novel Lancelot (1977), where songs and music deepen the reader experience of the cultural landscape of life and death. The present article combines methods of historically informed literary criticism and song analysis to examine Walker Percy’s presentation of life and death in the novel. The conclusion is that certain musical genres, such as popular music, folk song, and classical music are associated with particular manifestations of the cultures of life and death in the novel.